ANALISIS PENGARUH KEPEMILIKAN SAHAM OLEH PEMERINTAH, INSTITUSI NON PEMERINTAH, ASET DAN LEVERAGE TERHADAP KINERJA PASAR BUMN PRIVATISASI DI INDONESIA - Yuda Pamungkas; Fuad Fuad (Diponegoro Journal of Accounting, 2013)
This research's goal is to determine the nature of relationship between government ownership, private ownership, assets and leverage with the privatized State Owned Enterprise’s market performance. Previous studies indicate that these relationships are inconclusive. Therefore, it is necessary to conduct a forward research due to this inconclusiveness, and conclude the relationship between those variables with the SOE’s market performance. Population method performed in this research, by using all of the audited financial statements of privatized SOE in Indonesia from 2004-2011. By the total of one hundred and fourteen research objects being analyzed using linear regression to determine the relationship between variables such as government ownership, private ownership, assets and leverage with the SOE’s market performance. Results of this research indicate that determinants such as government ownership, assets and leverage affect the SOE’s market performance significantly with a non-linear convex, positive and negative relationship respectively. However, private ownership becomes the only determinant that does not explain the SOE’s low or high market performance.